Genetic structure of Argentinean hexaploid wheat germplasm - Vanzetti, Leonardo Sebastian (2013)
The identification of genetically homogeneous groups of individuals is an ancient issue in population genetics and in the case of crops like wheat, it can be valuable information for breeding programs, genetic mapping and germplasm resources. In this work we determined the genetic structure of a set of 102 Argentinean bread wheat (Triticum aestivum L.) elite cultivars using 38 biochemical and molecular markers (functional, closely linked to genes and neutral ones) distributed throughout 18 wheat chromosomes. Genetic relationships among these lines were examined using model-based clustering methods. In the analysis three subpopulations were identified which correspond largely to the origin of the germplasm used by the main breeding programs in Argentina.